Pengukuran Kinerja Dengan Pendekatan BSC Dan AHP Sebagai Alat Strategi Meningkatkan Kinerja Bandara XYZ - Akbar, M.Ali; Hariastuti , Ni Luh Putu (Universitas Nusantara PGRI Kediri, 2025)
XYZ Airport is a public sector organization operating in the service sector. The vision and mission of XYZ Airport is the realization of the provision of airport services in accordance with standards of safety, security and quality airport services that are reliable and competitive. To make this happen requires commitment from all parties. A good organization must understand and understand the internal strengths and weaknesses of the institution, therefore performance measurement is needed with the aim of knowing the extent to which organizational goals have been achieved and performance improvement. In this study, researchers chose performance measurement by applying the Balance Scorecard method as a strategic tool at XYZ Airport, integrated with the Government Agency Performance Report (LAKIP), which was then mapped into a mapping matrix of Customer, Financial, Internal Business and Learning and Growth Perspectives. From this perspective, weight is given using the Analytical Hierarchy Process method. The results of the measurement of the stakeholder perspective score of 42.5 achieved a good predicate (yellow), the financial perspective score of 15% received a bad predicate (red). 17% of the internal business process perspective received a good title (yellow), then 9% of the growth and learning perspective received a very good title (green). Based on these results, to achieve the goal, airports need to focus on strategic targets that are far from the target, including improving airport infrastructure to accommodate large-body aircraft as a lead indicator for increasing the number of passengers, aircraft movements and increasing PNBP.